Air untuk Daya Saing: Peran Strategis Bendungan dalam Meningkatkan PDRB Pertanian dan Perikanan untuk Ketahanan Pangan Regional - Muhammad Mufti Hudani,; Mega Mariska,; Nindya Eka Sobita,; Vitriyani Tri Purwaningsih, (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
Dams are crucial infrastructure for water resource management, serving as irrigation, flood control, raw water supply, energy, and food production. Systematically, dams can expand irrigated areas, enabling two to three planting seasons, and improving water availability throughout the seasons. East Java is a province with significant contributions to national GRDP through the agriculture, forestry, and fisheries sectors, particularly in food-producing districts. This study aims to evaluate the impact of the dams inaugurated in 2021 on the contribution of agricultural GRDP in each district in East Java Province. The results demonstrate that dams are effective in increasing GRDP growth in the agricultural sector of districts in East Java Province. Based on the regression results usingDifferent in Different(DiD) shows that the average GRDP growth in the agricultural sector of regencies in East Java province is higher by 0.011 percent compared to regencies without dams.